مقدرات التقلص ذوات المرحلة الواحدة والمرحلتين لدالة المعويه للتوزيع الاسي باستخدام العينات الكاملة - خليف علاء (University of Thi-Qar Journal of Science, 2008)
This paper we suggest some one & two stage shrunken estimators for reliability function of exponential distribution by using complete data .The shrunken factor is variable we find it by minimizing mean squared error for The suggest estimators .The bias, mean squared error and relative efficiency expressions are derived theoretically and assessed practically by using monte-carlo simulation . The results show the suggested estimators have better performance then classical estimators .